Parental perception of neonatal retro-transfers from level 3 to level 2 neonatal intensive care units. (12th December 2022) - Murthy, P.; Dosani, A.; Sikdar, K. C.; Koleade, A.; Rai, B.; Scotland, J.; Lodha, A.
Abstract: Objective: The primary objective of this study was to determine the overall parental satisfaction with retro-transfers from a level 3 to a level 2 Neonatal Intensive Care Unit (NICU). The secondary objectives were to explore factors that caused parental satisfaction associated with retro-transfer and investigate the factors that could be modified to improve the retro-transfer process. Methods: This is a retrospective cross-sectional study. Questionnaires were mailed to all parents of infants transferred from level 3 to level 2 NICUs from 2016 to 2017. Independent samples t-tests, Spearman's rank correlations, and multiple logistic regression analyses were conducted to identify factors associated with parental retro-transfer satisfaction. Results: Our response rate was 39.1% ( n = 140). Of all parents, 64.29% parents were extremely satisfied with the overall retro-transfer process. In our bivariate analyses, multiple factors were found to be strongly associated with parental retro-transfer satisfaction, including parental level of education, the amount of notice and rationale given for the retro-transfer and the level of parental communication and engagement with their infant's healthcare team before and after transfer. Multiple logistic regression analyses revealed that when questions regarding the retro-transfer were answered and the level 2 NICU team demonstrated a concrete understanding of the infant's medical issues and history, parental satisfaction increased. Conclusion: Majority of parents were satisfied with the retro-transfer process. However, close collaboration and ongoing and open lines of communication between parents and the level 3 NICU healthcare teams will increase parental retro-transfer satisfaction rates.